A season to celebrate [large type] - Michaels, Fern; Pearce, Kate, 1963-; Kauffman, Donna; Oliveras, Priscilla (Wheeler Publishing large print hardcover, 2018)
Fern Michaels and three other award-winning romance writers help to make it a merry Christmas with four stories of the special ways the holidays warm our hearts.